Kajian Literature: Urgensi Prinsip Komunikasi Islam dalam Mengatasi Hoax di Era 4.0. - Tahir, Muhammad; Rayhaniah, Sri Ayu; Halimah, Halimah (Borneo International Journal of Islamic Studies, 2021)
Technological developments in the 4.0 era need to be faced with an awareness of the importance of communication and digital literacy. The urgency is so that people can use digital media in a healthy, wise, intelligent, careful, precise, and law-abiding manner to avoid hoaxes. The use of media as a communication tool and the principle of communication itself needs attention and in-depth study, including in the study of Islamic communication. The meaning of Islamic communication is the delivery of Islamic messages using the communication principles in Islam. Islamic teachings, in this case, have explicitly provided guidelines, namely by prioritizing the concept of Islamic communication principles in daily life interactions, including communicating digitally in the 4.0 era. This article describes the urgency of Islamic communication principles in overcoming Hoaxes in Era 4.0. This study uses a design in the form of a literature study. This study is a qualitative study using document analysis methods. The results of the study state that several kinds of literature on the study of Islamic communication principles have been researched, starting from 2010-2020. That the study of Islamic communication principles in the 4.0 era must not only be understood by the public but also as a foundation in social media as well as fend off all things related to hoaxes.